Seismic performance analysis of Kuala Lumpur air traffic control tower by friction damper - Ong, Peng Pheng (2009)
In structural earthquake engineering, different kinds of energy absorption devices were invented during last 30 years (Guan et al, 2004). And more than one-decade research has shown that, on account of the virtue of no power requirement, rapid response and coulomb friction principle of friction damper is one of best of them. It is used as plating friction for energy dissipation systems to reduce earthquake effect on structures. With laminated steel plates and bolt, the friction damper can provide high diagonal stiffness and flexibility in horizontal direction to ensure the mounting forces can be supported by the stresses induced on the structure and prevent excessive sideways from any horizontal loading especially when earthquake occur. This research is to study the performance of Air Traffic Control Tower of Kuala Lumpur International Airport (KLIA Control Tower) under low intensity earthquake effect of induced earthquake acceleration of 0.19g. The finite element modelling technique is used in this study to learn the behaviour of friction damper and vulnerability of loading from vertical and horizontal directions with the proposed application. Performances of the friction damper were examined based on their percentile capacity passing and inter-storey drift displacement, consisting of Beam Models and Shell Models with and without friction damper. Friction damper is designed within the lift-core and it is found that the usage of designed retrofitted friction damper increases the overall performance of the KLIA Control Tower. In general, this study indicates that the seismic risks should be considered in designing the tower for Malaysia construction and the application of the seismic retrofitting to this existing building is much needed to safeguard structure from external peak ground acceleration intensity. Therefore, it is discovered from the final analysis the friction damper is able to stiffen the structure from seismic loading in term of deformation and axial force from the intensity of 019g, 0.29g and 0.39g.